Exploring the potential of common iceplant, seaside arrowgrass and sea fennel as edible halophytic plants. (November 2020) - Sánchez-Faure, Alicia; Calvo, Marta María; Pérez-Jiménez, Jara; Martín-Diana, Ana Belén; Rico, Daniel; Montero, María Pilar; Gómez-Guillén, María del Carmen; López-Caballero, María Elvira; Martínez-Alvarez, Oscar
Graphical abstract: Highlights: The halophytes are a good source of macroelements and microelements. Sea fennel had high dietary fibre content. Bioactive polyphenols and high PUFA/SFA ratio were found in the halophytes. Seaside arrowgrass showed high Fe levels and the presence of isoorientin. Hydroxycinnamic acids were predominant in Common iceplant and Sea fennel. Abstract: The recent interest in diversification in food consumption and the current salinization and desertification processes of farmland have placed the focus on halophytic plants as new food, making necessary the characterization of their biochemical composition and the identification of possible bioactive compounds. In this work, three edible halophytic plants were characterized: common iceplant ( Mesembryanthemum crystallinum ), sea fennel ( Crithmum maritimum ), and seaside arrowgrass ( Triglochin maritima ). The plants studied were a good source of minerals. Sea fennel showed high contents of dietary fibre and calcium (8.5 ppm, wet weight), common iceplant had a high potassium content (6500 ppm, wet weight), while seaside arrowgrass presented high levels of iron (62 ppm, wet weight). The glucose content of the three species was below 30 mg/g per dried weight. The Sb, Pb, Cr, As, Cd, and Hg content was negligible. Polyunsaturated fatty acids, mainly α-linolenic and linoleic acid, prevailed in the three species analyzed. Hydroxycinnamic and hydroxybenzoic acids predominated in common iceplant and sea fennel. Glycosylated flavones, especially isoorientin, prevailed in seaside arrowgrass. These plants present a relevant nutritional profile for which their use as foods or ingredients should be promoted.